STUDI PENGARUH SPASI DAN PANJANG GEOTEXTILE PADA PERKUATAN LERENG DIBAWAH PONDASI DANGKAL DENGAN PEMODELAN DI LABORATORIUM - Ikhromul Khoirul Aqshom; Arief Alihuedin; Suhartinah Suhartinah (HEXAGON, 2020)
The development of infrastructure in Indonesia has recently developed so rapidly that the need for land has increased to meet infrastructure development. This encourages humans to make the best use of the land, one of which is slopes and hilly areas. The safety of a slope is influenced by several factors, including the slope factor and the load that works on it. The high level of slope and large loads thatwork on it can trigger landslides so that a solution is needed to prevent it, one of which is reinforcing using a geotextile. To determine the performance of the geotextile as slope reinforcement, further research is needed on the effect of the length of the geotextile reinforcement (p) and the spacing between the geotextile (s).